Medvezhiy Glacier surge in 2011 - V. M. Kotlyakov; L. V. Desinov (Лëд и снег, 2015)
The paper presents results of monitoring of the Medvezhiy Glacier state for the period from its surge of 2001 to the last pulsation of 2011. This monitoring is performed based on the photographing made from the Russian section of the International Space Station. Features, used for prediction of the glacier last movement, are pointed out. The earlier determined characteristic property of the Medvezhiy Glacier change from a phase of recovering to that of its fast movement has been substantiated. Mean period of the glacier pulsations, estimated from observations for the last century, is 13.5 years. A surge of the glacier left tributary is recognized.